2015
DOI: 10.1016/j.pharep.2014.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Long-term disease-modifying effect of the endocannabinoid agonist WIN55,212-2 in a rat model of audiogenic epilepsy

Abstract: This result suggests that short-term potentiation of the eCB system might modify the epileptogenic disease process in patients with a progressive course of epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Chronic administration of the full CB 1 R agonist WIN55,212-2 (4 mg/kg/day, i.p., for 11 days, 30 min before stimulation) exhibited anti-epileptogenic properties in the amygdala kindling model of temporal lobe epilepsy in mice by delaying the progression of seizures severity [94]. A single dose of WIN55,212-2 (4 mg/kg, s.c.) administered at the start of the epileptogenic kindling process has also been shown to prolong seizures development by a period of two weeks in Krushinsky-Molodkina (KM) rats with genetic audiogenic epilepsy [95]. WIN 55,212-2 (10 μM) attenuated the frequency of excitatory postsynaptic currents in whole cell patch clamp recordings from granule cells in vitro and impeded recurrent excitation in the dentate gyrus of mice with pilocarpine-induced temporal lobe epilepsy (TLE), assessed after electric stimulation of mossy fibers in the hilus of hippocampal slices [96].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic administration of the full CB 1 R agonist WIN55,212-2 (4 mg/kg/day, i.p., for 11 days, 30 min before stimulation) exhibited anti-epileptogenic properties in the amygdala kindling model of temporal lobe epilepsy in mice by delaying the progression of seizures severity [94]. A single dose of WIN55,212-2 (4 mg/kg, s.c.) administered at the start of the epileptogenic kindling process has also been shown to prolong seizures development by a period of two weeks in Krushinsky-Molodkina (KM) rats with genetic audiogenic epilepsy [95]. WIN 55,212-2 (10 μM) attenuated the frequency of excitatory postsynaptic currents in whole cell patch clamp recordings from granule cells in vitro and impeded recurrent excitation in the dentate gyrus of mice with pilocarpine-induced temporal lobe epilepsy (TLE), assessed after electric stimulation of mossy fibers in the hilus of hippocampal slices [96].…”
Section: Resultsmentioning
confidence: 99%
“…Collectively, understanding the role of the endocannabinoid system in epileptogenesis requires careful consideration of the dosing schedule, time window of drug administration, age of the animal, and underlying seizures network [95]. CB 1 R agonists demonstrate primarily anticonvulsive effects in chronic models, while CB 1 R antagonists exert mixed effects, based on drug timing and dosage.…”
Section: Resultsmentioning
confidence: 99%
“…In turn, results obtained from the treatment with cannabinoids WIN 55,212-2 and 2-arachidonoylglycerol (2-AG) in the mouse olfactory epithelium in vivo indicated increased proliferation, but not neurogenesis nor non-neuronal cell generation [57]. Additionally, Vinogradowa and van Rijn [58] examined acute and long-term effects of another synthetic cannabinoid WIN55,212-2 in the early stage of audiogenic kindling. The results they obtained showed that WIN55,212-2 administered in a single dose one hour before the 4th seizure delayed the kindling process by two weeks, without any acute effect on audiogenic seizures.…”
Section: Discussionmentioning
confidence: 99%
“…Results from animal models for brain injuries suggest a seizure protective role of the endocannabinoid system. CB 1 agonists attenuate several types of seizures [18][19][20] and retard the development of amygdala kindling [21,22]. Additionally, the CB 1 agonist R(+)WIN55,212-2 (WIN) reduces status epilepticus and subsequent mortality in rats [23].…”
Section: Introductionmentioning
confidence: 99%